2008
DOI: 10.1097/ijg.0b013e31815a3472
|View full text |Cite
|
Sign up to set email alerts
|

Duration of IOP Reduction With Travoprost BAK-free Solution

Abstract: Travoprost without BAK has similar IOP-lowering efficacy and safety compared with travoprost preserved with BAK. Both formulations of travoprost have a prolonged duration of action, with statistically and clinically significant reductions from baseline persisting up to 60 hours after the last dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 21 publications
2
37
0
1
Order By: Relevance
“…that the two formulations of travoprost (travoprost with BAK and travoprost BAK-free) had similar effi cacy, including a prolonged duration of action showing Ͼ6 mmHg reduction in IOP 60 hours after fi nal dose of either drug (Gross et al 2008). However, physicians must interpret the effi cacy data from the current trial with caution because of its open-label design, which may have introduced bias into the results for IOP.…”
Section: Discussionmentioning
confidence: 85%
“…that the two formulations of travoprost (travoprost with BAK and travoprost BAK-free) had similar effi cacy, including a prolonged duration of action showing Ͼ6 mmHg reduction in IOP 60 hours after fi nal dose of either drug (Gross et al 2008). However, physicians must interpret the effi cacy data from the current trial with caution because of its open-label design, which may have introduced bias into the results for IOP.…”
Section: Discussionmentioning
confidence: 85%
“…[41][42][43] In particular, Hamacher et al 41 in a pharmacodynamics analysis did not find statistically significant differences between BAK-free and BAKcontaining formulations in the incidence of ocular adverse events comparing preservative-free tafluprost with tafluprost containing 0.01% BAK. Also, in the work of Gross et al 42 , travoprost BAK free and travoprost preserved with BAK showed no differences in the safety and Lewis et al 43 have demonstrated no differences in the incidence of side ocular effects, comparing travoprost 0.004% containing 0.015% BAK with travoprost 0.004% BAK free.…”
Section: Discussionmentioning
confidence: 99%
“…196,197 This results in a longer duration, clinically useful, IOP-lowering effect of both original travoprost and the BAK-free version. 180,198,199 This could be important in patients who occasionally miss doses. The functional activities of the HLs are shown in Fig.…”
Section: Hypotensive Lipidsmentioning
confidence: 98%